Security Analysis System E-learning at one of the University in Indonesia - Insanudin, Entik; Pudjoatmodjo, Bambang (International Journal of Engineering and Technology, 2019)
E-learning is one of the services that were developed massively in education. Therefore the application of the system security is also very taken into account, this is done in order to user comfort e-learning system mainly reflects the e-learning system for on-line or better known by the term e-learning. In this research, the authors attempted to analyze the security system e-learning at one of the universities in Indonesia by using the tools sniffing cain and abel to detect the vulnerability when a user e-learning while doing logged if the username and password is visible and tools Acunetix Web vulnerability scanner to analyze more remote security loopholes contained in e-learning system at one of the universities in Indonesia, In additions Acunetix Web Vulnerability scanning tools can inform the whole of each vulnerability found on e-learning system at one of the universities in Indonesia located on level 3 High, this shows that e-learning on one of the university is very vulnerable to threats.Â Â